The Sources and Magnitudes of Switzerland's Gains from Trade - Christian Hepenstrick (Swiss Journal of Economics and Statistics, 2016)
This paper uses the modern workhorse model of quantitative trade theory (Eaton and Kortum, 2002) as a measurement tool to quantify Switzerland's gains from trade. I find that individual trading partners matter surprisingly little for Switzerland's welfare because of reallocation effects: if trade between Switzerland and some partner country is inhibited, other supplier countries step into the breach so that the losses are limited andtypically amount to less than 1%. The conclusions are different if one considers groups of countries such as for example the EU: participating in a multilateral 25% trade cost reduction increases Swiss welfare by 11% relative to the status quo. However, it must also be noted that in the case of non-participation, the actual welfare losses relative to the status quo are modest with less than 1%.
Keywords: F10; F11; F14; 330; gains from trade; Switzerland; development accounting